A review of the subspecies of the Leach petrel, Oceanodroma leucorhoa (Vieillot) ... - Oberholser, Harry C. Harry Church, (Smithsonian Institution Press, [etc.], 1917)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided. ...